The influence of ice jams on ice-induced vibrations of multi-legged sub-structures - Lelieveld, Tim (author) (2021)
The world is transforming its energy production towards more sustainable sources of energy. In Europe, there is currently 25 GW of installed offshore wind power capacity. This is expected to grow with 29 GW over the next five years. Offshore wind farms can be expensive and challenging to build, design and maintain. Understanding the offshore environment will ensure that the to be produced offshore wind turbines are of sufficient quality while reducing costs. Monopiles are currently the most common sub-structure, but jacket sub-structures are becoming more relevant due to increasing water depth or changing soil conditions. Structures in icy waters, such as the Baltic Sea, may be subjected to ice induced vibrations while they encounter sea ice. These vibrations have to be considered in vertically-sided offshore structures' design and are the most critical load case when ice is concerned. Multi-legged sub-structures, such as jackets, can have a problem that does not exist for monopiles, namely ice jamming, where ice fills the space between the legs of a multi-legged sub-structure. The legs and the jammed ice may then act as a single structural unit. Which leads to the main research question: how does an ice jam influence ice-induced vibrations of a multi-legged sub-structure? First, a literature study of ice jams and multi-legged sub-structures was performed. This study concluded that different ice jamming situations are possible and have occurred with multi-legged structures, which not all have survived. The ratio between leg spacing and diameter plays a vital role in the ice action on multi-legged structures. Furthermore, the combination of ice-induced vibrations and ice jamming had not been studied yet. Secondly, a model is made based on a phenomenological ice crushing model using COMSOL Multiphysics and MATLAB to simulate the structural response. The sub-structure is based on the jacket design for the NREL 5-MW reference turbine. Different situations from the literature study are used to make several design ...